Peran Guru Akidah Akhlak Pada Pembentukan Karakter Siswa Di Era Industri 4.0 Di Mas Al-Ma'arif Gebang - Rizki Salsabila Ramadhan Maha (Cybernetics: Journal Educational Research and Social Studies, 2022)
Changes that occur in society today are increasingly advancing rapidly, this era is known as the industrial era 4.0 which is very influential in various fields, especially in Islamic religious education. The challenges that must be passed in order to achieve the goals of Islamic education are to create a generation of knowledge and piety. Morals are indispensable for every country is one of the great goals for the world of Islamic education. Islamic religious education in schools is known and focused on the subjects of moral aqidah and is at the same time a part of the life of the people in Indonesia. Akidah Akhlak education should be able to raise the quality of literacy in Indonesia because it is already listed in Q.S Al-Alaq. All of this is the basis of good Islamic character education used in education. This research was carried out with the objectives of 1) To find out the planning of the Aqeedah Akhlaq teacher in shaping the character of the 4.0 era at MAS Al-Ma'arif Gebang. 2) To find out the role of the Akhlaq teacher in shaping the character of the 4.0 era at MAS Al-Ma'arif Gebang.3 ) To find out the evaluation of moral creed teachers in the formation of character era 4.0 at MAS Al-Ma'arif Gebang. The method used in this study is a qualitative research method. Sources of data used are primary and secondary data, with interview procedures, documentation and observation. With the technique of transcription analysis, seduction, interpretation and data triangulation. The results of this study indicate that the learning planning process at Madrasah Aliyah Swasta Al-Ma'arif Gebang is always made by every teacher, including the teacher of moral aqidah. Preparation of learning tools such as syllabus, time allocation analysis, effective week, lesson plans have always been prepared by subject teachers. The formation of student character is good, the teacher's role is carried out in formation by incorporating current conditions into the learning concept. Evaluation is carried out at the end of each lesson, meaning like the end of each KD / Chapter in each lesson. The moral aqidah teacher has carried out his role to form good character in students.